Inked: Graduate Writing Groups as Writing Centre Pedagogy - Cournoyea, Michael; Samuels, Boba; Calloway, David (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
In the post-pandemic era, Canadian writing centres are ideally positioned to organise and support graduate writing groups. At the University of Toronto’s Health Sciences Writing Centre, we have begun offering a weekly, multidisciplinary graduate writing group for students in the health sciences. Inked: the Health Sciences Writing Collective aims to bridge the gap between high-commitment co-working groups and low-commitment accountability groups. We outline how the group emerged, how it addresses graduate challenges, and how it builds self-efficacy and community among members. We argue that this move to group-centred, indirect instruction presents an exciting direction for writing centre pedagogy in Canada.